Developing An English Textbook For Students of Computer Science - ernanda ernanda; yanto yanto (English Literature Department, Adab and Humanities Faculty, 2022)
The purpose of this research is to develop an English textbook for students of computer science. This research used ADDIE (Analyze, Design, Develop, Implement, Evaluate). The researchers followed the five steps of the research procedure to produce an English textbook. Students and lecturers were involved in this research. The materials in the book were based on students' needs and have been validated by the computer science lecturers. The product has also accommodated the four basic skills and can be used as a self-study book.